Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jso.26137
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions after ovarian cancer cytoreduction surgery: The first 30 days and beyond

Abstract: Background and Objectives: Postoperative readmissions are often used to assess quality of surgical care. This study compared 30-day vs 31-to 90-day readmission following surgery for ovarian, fallopian tube, or primary peritoneal cancer. Methods: This retrospective study of the 2010-2015 Nationwide Readmissions Database characterized 90-day readmissions following cytoreductive surgery for these cancers. Each patient's first postoperative hospitalization was included. Univariate analysis compared patient demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Hospital characteristics included teaching status, size, region, and urban or rural location. Hospitals were also categorized into tertiles based on operative volume using the annual number of endometrial cancer operations reported, as our group has implemented in prior database studies 17. Patients <18 years of age as well as those missing age, insurance, and survival data were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital characteristics included teaching status, size, region, and urban or rural location. Hospitals were also categorized into tertiles based on operative volume using the annual number of endometrial cancer operations reported, as our group has implemented in prior database studies 17. Patients <18 years of age as well as those missing age, insurance, and survival data were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The Elixhauser Comorbidity Index was used to assess the burden of chronic conditions. The Elixhauser Comorbidity Index algorithm uses ICD-9-CM and ICD-10-CM codes to identify 30 comorbidities thoroughly validated for use in administrative databases 17. Extended procedures were defined using methods previously published by Jones et al and encompassed any procedure involving concomitant resection of the stomach, spleen, liver, diaphragm, small or large bowel, or rectosigmoid colon, or any procedure resulting in ileostomy or colostomy 21…”
Section: Methodsmentioning
confidence: 99%
“…Modeled after previously published studies on postoperative outcomes in ovarian cancer surgery ( Wright et al, 2011 , Cham et al, 2019 , Kumar et al, 2016 ), the primary outcome was a 30-day morbidity composite, which included surgical complications (wound complication, intraperitoneal abscess, ileus, small bowel obstruction, bowel perforation, and reoperation within 30 days) and medical complications (venous thromboembolism, arrhythmia, myocardial infarction, pneumonia, cardiopulmonary arrest, and acute renal failure). Secondary outcomes were measures of increased healthcare utilization, including an extended hospital stay (defined as > 7 days) ( Mardock et al, 2020 ), intensive care unit admission, and 30-day hospital readmission; as well as progression-free and overall survival.…”
Section: Methodsmentioning
confidence: 99%
“…Venous thromboembolism events that require readmission are associated with significant cost and have a high risk of mortality . The 30-day readmission rate after complex cancer surgery varies from 10% to 15%, with approximately 2% to 4% of readmissions attributed to VTE . Because patients undergoing complex cancer surgery remain at extended risk for VTE, it is likely that readmissions owing to VTE also continue beyond 30 days.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The 30-day readmission rate after complex cancer surgery varies from 10% to 15%, with approximately 2% to 4% of readmissions attributed to VTE. [9][10][11][12][13] Because patients undergoing complex cancer surgery remain at extended risk for VTE, it is likely that readmissions owing to VTE also continue beyond 30 days. These severe VTE events are a potentially preventable delayed complication after complex cancer surgery.…”
mentioning
confidence: 99%